Gender and politics: the relevance of gender on judgements about the merit of candidates and the fairness of quotas - Santos, M. H. (2017)
Drawing on the conceptualization of meritocracy as an illusion, we argue that perceptions of merit and fairness of sex quotas in politics are influenced by gender ideology, specifically gender symbolical asymmetry, which equates men with individuals and the universal reference of 'person', and women with a sexed category. A total of 311 Portuguese participants read one of eight scenarios manipulating the sex and political competence of two candidates for an electoral list where only one would be selected. According to the experimental condition, either the female or the male candidate was presented as more competent or both candidates were presented as equally competent. In the control condition no such information was provided. Participants rated the merit of the selected candidate and the fairness of quotas. Results show that men take mostly only the candidates’ competence information into consideration. Reflecting gender symbolic asymmetry women were also influenced by the fact that the selected candidate was male or female. Results are discussed in the light of the gender symbolic asymmetry model.